Multiple strategic orientations and strategic flexibility in product innovation - Chen Han; Shuman Zhang (European Research on Management and Business Economics (ERMBE), 2021)
This research investigates how multiple strategic orientations and strategic flexibility collectively influ-ence firm product innovation. A chain multiple mediation model with moderation is constructed thatlinks two types of strategic orientation (entrepreneurial orientation and learning orientation) and twodimensions of strategic flexibility (resource flexibility and coordination flexibility) to product innovation.The model is tested by analysing paired survey responses collected from 303 Chinese firms with SPSSPROCESS Macro. The results show that entrepreneurial orientation stimulates firm product innovationthrough three parallel routes. First, entrepreneurial orientation improves product innovation by enhanc-ing learning orientation. Second, entrepreneurial orientation positively influences product innovationby boosting coordination flexibility. Third, entrepreneurial orientation strengthens product innovationthrough the chain mediating effects of learning orientation and coordination flexibility. Moreover, thechain multiple mediation model is positively moderated by resource flexibility.
Keywords: O32; 650; Multiple strategic orientations; Strategic flexibility; Product innovation